Comparative Gut Microbiome in Trachypithecus leucocephalus and Other Primates in Guangxi, China, Based on Metagenome Sequencing - Que, Tengcheng; Pang, Xianwu; Huang, Hongli; Chen, Panyu; Wei, Yinfeng; Hua, Yiming; Liao, Hongjun; Wu, Jianbao; Li, Shousheng; Wu, Aiqiong; He, Meihong; Ruan, Xiangdong; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
The Trachypithecus leucocephalus (white-headed langur) was a highly endangered, karst-endemic primate species, inhabiting the karst limestone forest in Guangxi, Southwest China. How white-headed langurs adapted to karst limestone and special dietary remained unclear. It was the first time to study the correlation between the gut microbiome of primates and special dietary, and environment in Guangxi. In the study, 150 fecal samples were collected from nine primates in Guangxi, China. Metagenomic sequencing were used to analyze and compare the gut microbiome composition and diversity between white-headed langurs and other primates. Our results indicated that white-headed langurs had a higher diversity of microbiome than other primates, and the key microbiome were phylum Firmicutes, class Clostridia, family Lachnospiraceae, genus Clostridiates and Ruminococcus, which were related to the digestion and degradation of cellulose. Ten genus were significantly more abundant in white-headed langurs and francois’s langur than in other primates, most of which were high-temperature microbiome. Functional analysis revealed that energy synthesis-related pathways and sugar metabolism-related pathways were less abundant in white-headed langurs and francois’s langur than in other primates. This phenomenon could be an adaptation mechanism of leaf-eating primates to low-energy diet. The gut microbiome of white-headed langurs was related to diet and karst limestone environment. This study could serve as a reference to design conservation breeding, manage conservation units, and determine conservation priorities.